Representation of solutions to Helmholtz's equation - Ramm, Alexander G. (My University, 1983)
It is proved that any potential of a single layer v is identically equal to a potential of a double layer w in the bounded domain, D, and a necessary and sufficient condition for v≡w in Ω=R³/D, the exterior domain, is given.
Keywords: Helmholtz's equation